Teacher Attrition and Retention: A Meta-Analytic and Narrative Review of the Research - Borman, Geoffrey D.; Dowling, N. Maritza (Review of Educational Research, 2008)
This comprehensive meta-analysis on teacher career trajectories, consisting of 34 studies of 63 attrition moderators, seeks to understand why teaching attrition occurs, or what factors moderate attrition outcomes. Personal characteristics of teachers are important predictors of turnover. Attributes of teachers’ schools, including organizational characteristics, student body composition, and resources (instructional spending and teacher salaries), are also key moderators. The evidence suggests that attrition from teaching is (a) not necessarily “healthy” turnover, (b) influenced by various personal and professional factors that change across teachers’ career paths, (c) more strongly moderated by characteristics of teachers’ work conditions than previously noted in the literature, and (d) a problem that can be addressed through policies and initiatives. Though researchers have utilized a number of national and state databases and have applied economic labor theory to questions related to teacher attrition, the authors argue that better longitudinal data on teacher career paths and more nuanced theories are needed.